Trajectory design and control of an unmanned aerial vehicle for efficient crop irrigation (2018)
This paper addresses the issue of efficient crop irrigation from the perspective of precision agriculture, motivated by the need to make agriculture more sustainable. In this paper we design both the trajectory to be followed and the high level control for agricultural Unmanned Aerial Vehicles (UAVs). The irrigation results of this paper are extensive to any liquid being irrigated whether it is water, pesticides, insecticides or fertilizers. The main goal is to minimize the volume of liquid used while meeting the crop's needs. The methodology for trajectory design supposes regular grid paths but not constant speed or acceleration. We do not make any assumptions on the speed, and the fact that it varies according to the crop?s conditions is what allows for precision irrigation to be achieved. Simulation results have shown that significant amounts of liquid can be saved by applying this irrigation methodology. The input for the trajectory design methodology is an image of a vegetation index such as the Crop Water Stress Index (CWSI) or the Normalized Difference Vegetation Index (NDVI). The output is the group of position functions to be followed. This paper also shows the development of a theorem which states the maximum bound on the tracking error, given a state feedback control law. Finally a LQR control is implemented and results show almost no tracking error.